Multi-faith activity assemblies : 90 + ideas for primary schools - Peirce, Elizabeth, 1946- (RoutledgeFalmer, 2003)
Packed with ideas for the primary school teacher, this book includes stories, songs and drama activities from six major world religions: Christianity, Buddhism, Hinduism, Islam, Judaism and Sikhism. The book is helpfully split into topic areas which include:New BeginningsPlaces of WorshipFriendsFestivalsRites of PassageWater ThemesAnimals and BirdsInspirational Leaders. There is also a useful section on background information with pronunciation guides for teachers for the different world religions feature.